PENGEMBANGAN E-LKPD LIVEWORKSHEET BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS V MATA PELAJARAN IPAS - RATNAWATI, YULIANA CANDRA; Hari Subiyantoro; Moh Gufron (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop an e-LKPD using the Liveworksheet platform integrated with a Problem Based Learning (PBL) model to improve student learning outcomes in the IPAS subject for Grade V elementary students. The study applied the ADDIE development model with five stages: analysis, design, development, implementation, and evaluation. Data were obtained through validation sheets, observation, questionnaires, and pretest-posttest assessments. The developed e-LKPD was declared very valid based on expert reviews, observation of learning activities, and effective based on increased student learning outcomes. This research contributes to the development of digital learning media that integrate real-world problem-solving in IPAS subjects, especially under the Merdeka Curriculum framework.